Oral cyanocobalamin supplementation in older people with vitamin B12 deficiency: a dose-finding trial. - Eussen, S; de Groot, L; Clarke, R; Schneede, J; Ueland, P; Hoefnagels, W; van Staveren, W (2005)
BACKGROUND: Supplementation with high doses of oral cobalamin is as effective as cobalamin administered by intramuscular injection to correct plasma markers of vitamin B(12) deficiency, but the effects of lower oral doses of cobalamin on such markers are uncertain. METHODS: We conducted a randomized, parallel-group, double-blind, dose-finding trial to determine the lowest oral dose of cyanocobalamin required to normalize biochemical markers of vitamin B(12) deficiency in older people with mild vitamin B(12) deficiency, defined as a serum vitamin B(12) level of 100 to 300 pmol/L (135-406 pg/mL) and a methylmalonic acid level of 0.26 mumol/L or greater. We assessed the effects of daily oral doses of 2.5, 100, 250, 500, and 1000 mug of cyanocobalamin administered for 16 weeks on biochemical markers of vitamin B(12) deficiency in 120 people. The main outcome measure was the dose of oral cyanocobalamin that produced 80% to 90% of the estimated maximal reduction in the plasma methylmalonic acid concentration. RESULTS: Supplementation with cyanocobalamin in daily oral doses of 2.5, 100, 250, 500, and 1000 mug was associated with mean reductions in plasma methylmalonic acid concentrations of 16%, 16%, 23%, 33%, and 33%, respectively. Daily doses of 647 to 1032 mug of cyanocobalamin were associated with 80% to 90% of the estimated maximum reduction in the plasma methylmalonic acid concentration. CONCLUSION: The lowest dose of oral cyanocobalamin required to normalize mild vitamin B(12) deficiency is more than 200 times greater than the recommended dietary allowance, which is approximately 3 mug daily.